Development of Performance Assessment of Learning Instruments Apply Daily Make-Up for Make Up Department at Vocational High School (Journal of Research and Educational Research Evaluation, 2018)
This research has not been effected by the presence of learning performance assessment instruments apply daily makeup standards, haven't tested the validity or reliability. Moreover the assessment instrument Competency Skills Exam of BSNP one indicator is less detailed, less range and scale criteria in section is too long so that the teachers feel difficulty in judging. The purpose of the research is to produce a performance assessment of learning instruments apply daily makeup valid, reliability and practical. This research is the development of research conducted at SMK Perwari Kendal, SMKN 6 Semarang, SMK Taman Siswa Kudus, SMK PGRI 1 Mejobo Kudus. The subject of this research is the 95 respondents. Test the validity of the content using the formula of Aiken's V and test reliability using the ICC. At trial, reliability, analyzed using Cronbach Alpha. Test the validity of invalid constructs using Confirmatory Factor Analysis (CFA) was formed of 3 factors i.e. factor 1 (pra practice), a factor of 2 (practice) and factor 3 (post practice). Test the practicality of the instrument indicates that the performance assessment instruments are very practical for use. The profile shows the performance capability of the students has the capability of excellent performance. Based on the results of the analysis, this research produces a valid performance assessment instruments, reliability and practical. The benefits of this research is a guide that can be used raw in measuring student performance in learning daily make-up.